thumbpins, 2005-2006 - Hermant, Emily (UnderCurrents: Journal of Critical Environmental Studies, 2006)
In this project, I ask: are we at war for control of our security, our privacy, our identity? I began by using the fingerprint to intervene in the public sphere. I enlarged my own thumbprint and began leaving a silkscreened version of it in public spaces such as windows, and bus shelters. I went on to create silkscreened textiles with the thumbprint pattern, using an army green camouflage motif.